(untitled) (diségno, 2021)
Now in its second year, the Summer School After the Damages not only confirms and strengthens the Higher Education project on the management of disaster or calamitous events and their impact on the built environment, but launches an International Academy aimed at promoting an interdisciplinary and integrated approach through a range of events. [read more]